Optical transformation of a CdTe quantum dot-based paper sensor for a visual fluorescence immunoassay induced by dissolved silver ions. Issue 4 (9th January 2017) - Lin, Zhenzhen; Lv, Shuzhen; Zhang, Kangyao; Tang, Dianping
Abstract : This work designs a visual fluorescence immunoassay for carcinoembryonic antigen based on structural and optical transformation of CdTe quantum dots immobilized on paper by cation-exchange reaction. Abstract : This work designs a simple low-cost visual fluorescence immunoassay for disease-related biomarkers (carcinoembryonic antigen, CEA, used as a model protein) in biological fluids, based on the structural and optical transformation of CdTe quantum dots (QDs) immobilized on paper induced by dissolved silver ions (Ag + ) from silver nanoparticles (AgNPs) via a cation-exchange reaction. A sandwich-type immunoreaction was initially carried out in a removable polystyrene high-binding microplate coated with monoclonal anti-CEA capture antibody by using AgNP-labeled polyclonal anti-CEA antibody as the detection antibody. Thereafter, the carried AgNPs accompanying the sandwiched immunocomplexes were dissolved by acid to release numerous silver ions, which induced the ion-exchange reaction with the immobilized CdTe QDs on the paper (attached onto the microplate lid) for the Cd-to-Ag transformation, thus resulting in the quenching of the visual fluorescence from the CdTe QDs owing to Ag2 Te formation. Under optimal conditions, the fluorescence intensity decreased with the increasing CEA concentration from 0.02 to 50 ng mL −1 with a detection limit of 5.6 pg mL −1 . Further, a visual assay based on a CdTe QD-based paper sensor was developed for CEA detection, and 5.0 pg mL −1 CEA could be discriminated with the naked eye. In addition, our strategy displayed high specificity, good reproducibility and acceptable accuracy for analyzing human serum specimens with consistent results obtained using the commercialized enzyme-linked immunosorbent assay (ELISA) method.